Water Consumption Status in Lalitpur Sub-Metropolitian City Area in Nepal - Poudel, Govinda Prasad (Journal of the Institute of Engineering, 2011)
This research is undertaken with main objectives of surveying and analyzing the present condition of public’s water consumption pattern from different water sources in Lalitpur sub-metropolitan city area. This is entirely based on field research and various steps of field research tools were used. Field observation and Key Informant Survey were carried out to collect for general data of the water sources and then to categorize them on the basis of their performance. Structured questionnaire survey was the undertaken with the users to assess the water use. Comparing different scenarios and results from users survey it is find that maximum 33% of demand fulfil by NWSC-supply, 7% fulfil by private well, 3% fulfil by neighbours well, 10% fulfil by public well 10 % fulfil by tanker supply, 3 % fulfil by rain water and 7 % fulfil by NWSC-Collection tank and 27% water demand fulfil by traditional stone spouts. Per capita water consumption of the users vary from a max 49 Lpcd to a minimum is 29 lpcd. This is mainly fulfilled by NWSC- supply, well, tanker supply and NWSC collection tank provided in different place in LSMC area and stone spouts. Key words: Public's water consumption; NWSC collection; Lalitpur Sub-Metropolitian City DOI: http://dx.doi.org/10.3126/jie.v8i1-2.5109 Journal of the Institute of Engineering Vol. 8, No. 1&2, 2010/2011 Page: 174-177 Uploaded Date: 20 July, 2011